A nitrogen isoscape of phytoplankton in the western North Pacific created with a marine nitrogen isotope model - Chisato Yoshikawa; Masahito Shigemitsu; Akitomo Yamamoto; Akira Oka; Naohiko Ohkouchi (Frontiers in Marine Science, 2024)
The nitrogen isotopic composition (δ15N) of phytoplankton varies substantially in the ocean reflecting biogeochemical processes such as N2 fixation, denitrification, and nitrate assimilation by phytoplankton. The δ15N values of zooplankton or fish inherit the values of the phytoplankton on which they feed. Combining δ15N values of marine organisms with a map of δ15N values (i.e., a nitrogen isoscape) of phytoplankton can reveal the habitat of marine organisms. Remarkable progress has been made in reconstructing time-series of δ15N values of migratory fish from various tissues, such as otoliths, fish scales, vertebrae, and eye lenses. However, there are no accurate nitrogen isoscapes of phytoplankton due to observational heterogeneity, preventing improvement in the accuracy of estimating migratory routes using the fish δ15N values. Here we present a nitrogen isoscape of phytoplankton in the western North Pacific created with a nitrogen isotope model. The simulated phytoplankton is relatively depleted in 15N at the subtropical site (annual average δ15N value of phytoplankton of 0.6‰), where N2 fixation occurs, and at the subarctic site (2.1‰), where nitrate assimilation by phytoplankton is low due to iron limitation. The simulated phytoplankton is enriched in 15N at the Kuroshio–Oyashio transition site (3.9‰), where nitrate utilization is high, and in the region around the Bering Strait site (6.7‰), where partial nitrification and benthic denitrification occur. The simulated δ15N distributions of nitrate, phytoplankton, and particulate organic nitrogen are consistent with δ15N observations in the western North Pacific. The seamless nitrogen isoscapes created in this study can be used to improve our understanding of the habitat of marine organisms or fish migration in the western North Pacific.